Influencia de apego y su repercusión en la estructura psíquico-emocional del niño en la primera infancia: investigación desde la perspectiva psicoanalítica - Guerrero Terán, Hilda Mercedes (2009)
Attachment is a special and specific bond that starts forming before a child is born between mother and child and remains throughout there lives. The theory of tachment is relatively new, but is a theme that has been talked about long ago, it was known as mother-child relationship, now known as affectionate joining. There are different conducts of attachment as for the child as for the mother, they are demonstrations of the need for fisical contact and psychological, of the thoughts and feelings that they have between them the couple. To how she reacts to these behaviors and which she shows or gives to her child, especially during his first infancy, depends in part to on the psiqui health and emotions of the infant; children that had a sure attachment from there mothers, this has influenced positively in his adult life and the ones without the joy of her presence especially in the first five years, present problems in there future relations, mental health and parenting, as many studies differ. The cuality of his attachment in the maturely born as to the prematurely born is of much import for the growth of the child, from his psychological development, and development of his yo, and overcoming the complex of Edipo, from the process of sexual differentiation, from the latencia period in other words in every step of infancy, of which the first years the most crucial, because this is where the bases of his personality are formed, from social interaction, to same forms of conduct that persist, where he starts to reorganize what pleases or displeases him, he adquires experiences, is given a meanigfull psychological growth and adquires all this from his mother. For his reason it is necessary that the mother has an adecuate mental health, with the support of her husband and immediate family. It is important on how she has taken care of herself during pregnancy to receive her child and how she developes her role as mother this will also influence his personality and character.